Relevant Management Aspects of Health Tourism Networking - Banevičius, Šarūnas (Socialiniai tyrimai, 2019)
The article deals with the process, concept, system and management aspects of health tourism networking. Addressing the problem of research: how to manage the networking process in health tourism. Summarizing the analysed scientific literature it can be stated that the participants of the network are not analysed individually. They are analysed in relation to other network participants, thus connecting them to a common system. Connections (links, interactions, contacts) between participants are a kind of interaction between two or more participants in a network when resources are transmitted over specific channels. Relationship is a concept that encompasses both form and content aspects. The dyadic level explores the nature of the connection between two or more network nodes. Examining the aspects of networking process management highlights the importance of strategic management and synergies with management theories: Fayol (administrative theory); agent-contract theory for networking partnerships. The aspects of management theories have applicability in the management of health tourism networking, and the decision-making process plays a crucial role – both individual and group decision making begins with a set of information that defines the situation, assesses expected benefits, anticipates possible choices, and possible consequences. The decision-making process ends with the choice of a specific alternative. By applying the CMO configuration model to the decision making process, a systematic solution mechanism is created for each problematic situation. In order for the Lithuanian health tourism segment and its organizations to function as an integrated system and develop along the path of sustainable development, it is expedient to develop a common strategy in the planning process, envisaging the vision, goals and objectives of Lithuanian health tourism and ensuring a feedback mechanism. To implement this process, it is recommended that a formal health tourism network (involving health service organizations, the scientific community) would be established, based on participant agreements. The aim of this network is to create and develop a variety of health tourism services. The resulting networks are formalized through contracts, legal acts, memoranda of understanding, general agreements, so the relationships, functions and responsibilities of their participants are clearly defined.
Keywords: health tourism; management theory; networking process